Efektivitas Biaya Pengiriman Pada Perusahaan Kulit Sapi dengan Menggunakan Metode Transportasi - Agti Pribatiwi; Tanjung Sekar Hayu Kinasih; Salma Azura; Talitha Ega Prasista; Titis Purwaningrum (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study explains about transportation methods which are part of operations research and involve minimizing costs from source to destination. Solving transportation problems in this case uses an applied method approach. The application integrated into field research is that researchers are directly in the company environment to collect data that will be applied in this study. The purpose of this study is to determine the results of product distribution calculations. The results of this study are that the most expensive product distribution calculation is at 500,000. Meanwhile, the results of the most expensive product distribution calculation are at 100,000. Cost optimization has an impact on the level of cost efficiency incurred by UD Manunggal Jaya.